Analyzing the Impact and Efficiency of Production Factors in Organic Rice Farming: A Case Study of Kediri Regency, Indonesia - Ahmad Rifki Hamdani; Fithri Mufriantie; M. Zul Mazwan (Universitas Muhammadiyah Malang, 2025)
The persistent expansion of organic rice farming in Kediri Regency has prompted farmers to adopt diverse cultivation practices. This study investigates the impact and efficiency of key production factors within this sector. Conducted in 2023, the research employed a census method to gather data from 30 organic rice farmers across five farmer groups in four sub-districts: Badas, Semen, Plosoklaten, and Purwoasri. We collected primary data through structured interviews and analyzed it using both the Cobb-Douglas and Stochastic Frontier production functions. Our findings indicate that three factors land area, organic fertilizer application, and farmer latest education level exert a significant positive effect on organic rice output. The regression model explains 92.4% of the variation in production (R² = 0.924). Furthermore, the analysis reveals that the current use of production factors is technically inefficient, with a mean efficiency score of 0.73, significantly below the optimal threshold of 1.00. These results underscore the potential for enhancing productivity in Kediri's organic rice sector through improved resource allocation.